Substrate Inhibition of 5β-Δ4-3-Ketosteroid Dehydrogenase in Sphingobium sp. Strain Chol11 Acts as Circuit Breaker During Growth With Toxic Bile Salts - Feller, Franziska M.; Marke, Gina; Drees, Steffen L.; Wöhlbrand, Lars; Rabus, Ralf; Philipp, Bodo (Frontiers in Microbiology, 2021)
In contrast to many steroid hormones and cholesterol, mammalian bile salts are 5β-steroids, which leads to a bent structure of the steroid core. Bile salts are surface-active steroids excreted into the environment in large amounts, where they are subject to bacterial degradation. Bacterial steroid degradation is initiated by the oxidation of the A-ring leading to canonical Δ4-3-keto steroids with a double bond in the A-ring. For 5β-bile salts, this Δ4-double bond is introduced into 3-keto-bile salts by a 5β-Δ4-ketosteroid dehydrogenase (5β-Δ4-KSTD). With the Nov2c019 protein from bile-salt degrading Sphingobium sp. strain Chol11, a novel 5β-Δ4-KSTD for bile-salt degradation belonging to the old yellow enzyme family was identified and named 5β-Δ4-KSTD1. By heterologous production in E. coli, 5β-Δ4-KSTD function could be shown for 5β-Δ4-KSTD1 as well as the homolog CasH from bile-salt degrading Rhodococcus jostii RHA1. The deletion mutant of 5β-Δ4-kstd1 had a prolonged lag-phase with cholate as sole carbon source and, in accordance with the function of 5β-Δ4-KSTD1, showed delayed 3-ketocholate transformation. Purified 5β-Δ4-KSTD1 was specific for 5β-steroids in contrast to 5α-steroids and converted steroids with a variety of hydroxy groups regardless of the presence of a side chain. 5β-Δ4-KSTD1 showed a relatively low Km for 3-ketocholate, a very high specific activity and pronounced substrate inhibition. With respect to the toxicity of bile salts, these kinetic properties indicate that 5β-Δ4-KSTD1 can achieve fast detoxification of the detergent character as well as prevention of an overflow of the catabolic pathway in presence of increased bile-salt concentrations.